FACTORS AFFECTING THE RELIABILITY AND DURABILITY OF RAILWAY WHEELS - Vakulenko, I. O.; Reidemeister, H. V.; Perkov, O. M. (Science and Transport Progress, 2005)
Factors have been examined that influence the strength parameters and other characteristics of railway wheels.